Synthesis of Cefdinir from 7-Amino-3-vinyl Cephem-4-carboxylic Acid Using N-Methyl Morpholine as Base - Muralikrishna, D.; Chetia, Apurba; Pagar, Vijay (Asian Journal of Chemistry, 2010)
In this paper, synthesis of cefdinir (I) from 7-amino-3- vinyl cephem-4-carboxylic acid (V) is reported by reacting with 2-mercapto benzothiazolyl (Z)-2-(2-amino-4-thiazolyl)- 2-acetoxyimino acetate (IV) in presence of base, N-methyl morpholine.